2022
DOI: 10.3389/fonc.2022.951310
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of BRCA 1/2 Genetic Test and Preventive Strategies: Using Real-World Data From an Upper-Middle Income Country

Abstract: Although BRCA1/2 genetic testing in developed countries is part of the reality for high-risk patients for hereditary breast and ovarian cancer (HBOC), the same is not true for upper-middle-income countries. For that reason, this study aimed to evaluate whether the BRCA1/2 genetic test and preventive strategies for women at high risk for HBOC are cost-effective compared to not performing these strategies in an upper-middle-income country. Adopting a payer perspective, a Markov model with a time horizon of 70 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(51 citation statements)
references
References 42 publications
(81 reference statements)
0
50
0
1
Order By: Relevance
“…No additional relevant studies were found through the reference lists of the included studies. Ultimately, only six articles met all the inclusion criteria which allowed for data extraction and quality assessment [ 35 40 ]. Figure 1 , the PRISMA 2020 flow diagram, provides a detailed summary of the selection process.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…No additional relevant studies were found through the reference lists of the included studies. Ultimately, only six articles met all the inclusion criteria which allowed for data extraction and quality assessment [ 35 40 ]. Figure 1 , the PRISMA 2020 flow diagram, provides a detailed summary of the selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 demonstrates the key characteristics of the included studies [ 35 40 ]. The economic evaluations conducted in LMICs primarily originated from upper-middle-income countries (Upper MICs) like China ( n = 2) Brazil ( n = 2) and Malaysia ( n = 1) [ 35 , 36 , 38 40 ] with only one study encompassed multiple countries with varying income levels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations